2020
DOI: 10.1021/acs.jmedchem.9b02025
|View full text |Cite
|
Sign up to set email alerts
|

Novel Stapling by Lysine Tethering Provides Stable and Low Hemolytic Cationic Antimicrobial Peptides

Abstract: Cationic antimicrobial peptides (CAMPs) are potent therapeutics for drug-resistant bacterial infections. However, the clinical application of CAMPs is hampered by its poor proteolytic stability and hemolytic activity toward eukaryotic cells. Great efforts have been made to design and generate derivatives of CAMPs with improved pharmacological properties. Here, we report a novel stapling protocol, which tethers two ε-amino groups of the lysine residue by the N-alkylation reaction on the hydrophilic face of amph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…426 An alternative one component approach includes disulfide or amide bond formation, and two-component techniques include S N Ar reactions of Cys residues and perfluoroaryl electrophiles, thioether formation, and alkylation of Lys residues. 426,[463][464][465]…”
Section: Stapled Amps (Stamps)mentioning
confidence: 99%
“…426 An alternative one component approach includes disulfide or amide bond formation, and two-component techniques include S N Ar reactions of Cys residues and perfluoroaryl electrophiles, thioether formation, and alkylation of Lys residues. 426,[463][464][465]…”
Section: Stapled Amps (Stamps)mentioning
confidence: 99%
“…Briefly, the cells were seeded at a density of 8,000 cells per well in a 96-well plate and cultured for 24 h in Dulbecco's Modified Eagle Medium (DMEM, Gibco) supplemented with 10% fetal bovine serum (FBS, Gibco), 2 mM L-glutamine, 100 U ml −1 penicillin, 100 mg ml −1 streptomycin (1% P/S, Invitrogen TM ), and at 37 • C in a 5% of CO 2 atmosphere. Then, different concentrations of the peptide (0, 10, 20, 30, and 40 µg ml −1 ) were added into each well and co-incubated with the cells for 24 h. After 2 h incubation with 10 µM 2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium (CCK-8, Yeasen, China), the cytotoxicity of the peptide was determined by measuring the optical density at 450 nm (Wu et al, 2014;Li et al, 2020).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…In recent studies, many attempts have been made to improve the performance of CαAMPs. These strategies involve re-engineering natural CαAMP sequences by site-directed mutation (Ahmad et al, 2009;Irazazabal et al, 2016;Li et al, 2016;Jiang et al, 2020), fragmentation (Luo et al, 2021) or chemical modification (Zarina and Nanda, 2014;Nayak et al, 2018;Mourtada et al, 2019;Mwangi et al, 2019;Li et al, 2020), computational approaches based on natural templates and statistical analysis (Loose et al, 2006;Nagarajan et al, 2018Nagarajan et al, , 2019, or designing de novo sequences by using simple alkaline vs hydrophobic amino acid combinations (Deslouches et al, 2005(Deslouches et al, , 2013Hu et al, 2011;Lakshmaiah Narayana et al, 2020). However, partly due to the complexity of the structure-activity relationships, which are derived from the sequence diversity of the peptides, progress in CαAMP optimization is still very limited and few CαAMPs have successfully achieved FDA approval (Greber and Dawgul, 2017;Ghosh et al, 2019;Torres et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported that the introduction of an N-alkylated crosslinker between the ipositioned Lys and the i + 4-positioned Lys enhanced helix stability and increased antimicrobial activity. [56] Furthermore, the stapled peptides also showed high serum stability and low hemolytic activity. Ni and Wang demonstrated that 1,2,3triazole stapling by Cu-catalyzed azide-alkyne cycloaddition represented a promising strategy to develop prominent AMPs.…”
Section: Side-chain Staplingmentioning
confidence: 99%